Eur Oral Res 2020
DOI: 10.26650/eor.20200032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixed dental prosthesis on the brain functions of partially edentulous patients – pilot study with power spectrum density analysis

Abstract: Purpose: This study was done to analyse the influence of fixed dental prosthesis (FDP) on brain function by analysing power spectral density of partially edentulous patients. Materials and methods: The study included unilateral missing mandibular molar replacement patients. The patients were restored with three-unit metal ceramic FDP restorations. The cognitive function was analysed with a mental state questionnaire. Power spectral density (PSD) analysis of EEG alpha wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A balanced development of occlusal forces is in fact associated with better cognitive conditions in older people [7]. It has also been shown, in subjects between 25 and 35 years with right molar loss that restoration of occlusal surface modifies EEG alpha rhythm, thus interfering with the mechanisms of attentive control [8]. Animal studies indicated that unilateral chewing is detrimental to spatial learning and leads to a decrease in the levels of serotonin and BDNF at the hippocampal level [9].…”
Section: Introductionmentioning
confidence: 99%
“…A balanced development of occlusal forces is in fact associated with better cognitive conditions in older people [7]. It has also been shown, in subjects between 25 and 35 years with right molar loss that restoration of occlusal surface modifies EEG alpha rhythm, thus interfering with the mechanisms of attentive control [8]. Animal studies indicated that unilateral chewing is detrimental to spatial learning and leads to a decrease in the levels of serotonin and BDNF at the hippocampal level [9].…”
Section: Introductionmentioning
confidence: 99%